OP01 Comparison of fecal transplantation, fecal transplantation with the novel UC diet or the UC diet alone for Refractory Mild to Moderate Active Ulcerative Colitis: The CRAFT UC randomized controlled trial. (27th May 2021) - Levine, A; Scaldaferri, F; Sarbagili Shabat, C; Zittan, E; Hirsch, A; Mentella, M C; Musca, T; Cohen, N A; Ron, Y; Fliss Isakov, N; Pfeffer, J; Yaakov, M; et al.
Abstract: Background: We evaluated if integration of novel diets for donors and patients in addition to fecal transplantation (FT) could increase FT remission in refractory ulcerative colitis (UC) or have an independent effect on remission. We developed a novel diet specifically designed for the dysbiosis of UC and to decrease factors that impair goblet cells or mucous production. Methods: This was a blinded randomized controlled pilot trial in adults with UC, defined by a simple clinical colitis activity index (SCCAI) of ≥5 and < 11 and endoscopic Mayo score 2–3, refractory to medication. Group 1 received free diet and standard FT by colonoscopy on day 1 and rectal enemas from a single donor on days 2 and 14 without dietary conditioning of the donor. Group 2 : FT as above but with dietary pre-conditioning of the donor for 14 days and a diet (UC Diet- UCD) for the patients after FT. Group 3 received the UC Diet alone without FT. Patients underwent a repeat endoscopy at week 8. The primary endpoint was clinical steroid free remission, defined as SCCAI <3, at week 8. Results: Fifty-one of the 96 planned patients were enrolled. The mean age was 40.4 ±12.5 years, 28/51(54.9%) had failed a biologic, 15/40 (29.4%) were on steroids at enrolment. Remission week 8 in Group 1 was 2/17(11.8%), Group 2 was 4/19 (21.1%), and 6/15 (40%) Group 3 (NS). Endoscopic remission was present in Group 1 : 2/17(12%), Group 2: 3/19(16%) and 4/15 (27%) Group 3 . Mucosal healing (Mayo 0) was achieved only in Group 3 (3/15, 20%) vs. 0/36 patients receiving FT (P=0.022). Exacerbation of disease occurred in 3/17 (17.6%) Group1, 4/19 (21.1%) Group 2, and 1/15 (6.7%) Group 3 (NS). The study was stopped for futility by a safety monitoring board. Conclusion: Fecal transplantation was not effective in this UC cohort. A UC Diet alone appeared to achieve higher clinical remission (40%) and mucosal healing than single donor FT with or without diet in mild to moderate UC failing medical therapy. This diet should be investigated further in a RCT specifically designed for the UCD. This study was supported by an ECCO Pioneer grant